Rancang Bangun Website Travel Umroh Berbasis Web Sebagai Media Informasi dan Digital Trust - Rahmad Saputra; Muliyono Muliyono; Yassirli Amri; Nurhidayat Nurhidayat (Jurnal Ilmu Komputer dan Sistem Informasi, 2025)
Umrah travel business is a service sector that strongly depends on the trust of prospective pilgrims. Therefore, service providers need an official information medium that is transparent, easily accessible, and able to validate the company’s identity. This study aims to design and develop a web-based umrah travel website as an information medium and a supporting platform for digital trust at Harira Tour and Travel. The system development method used in this study is the prototype method, consisting of requirement gathering, design, implementation, evaluation, and testing stages. The website was developed using WordPress CMS with several main features, including homepage, company profile, umrah packages, gallery, testimonials, contact information, and WhatsApp integration. The results show that the website is able to present service information in a structured manner, provide responsive access on desktop and mobile devices, and help prospective pilgrims obtain official information more easily. Black box testing on 9 main features shows that all features function according to the functional requirements with a success rate of 100%. This website supports digital trust through company identity, transparent package information, activity documentation, testimonials, and official communication channels.